Preliminary investigation and design considerations for the rehabilitation of trash screen at jor reservoir low level outlet - Jansen L.; Sidek L.M.; Julien P.Y. (Trans Tech Publications Ltd, 2023)
Jor reservoir was constructed to assure flow regulation for the Woh hydroelectric power station, as well as to provide storage for flood control. The reservoir outlet is frequently operated once every three months to flush the deposited sediments accumulated within the reservoir. Preliminary testing and inspection on the reservoir outlet revealed that the trash screen located at upstream of reservoir outlet had been damaged and dislodged creating a large opening at the trash screen thus permitting entry of larger logs which blocks the passage of water through the reservoir outlet. Bathymetric survey showed the total height of sediment deposition above the reservoir outlet covering the trash screen was estimated at approximately 13 m. The sediment volume estimated to be cleared from above the reservoir outlet area is 15,000 m3. Soil investigation conducted shows that the sediments deposited within the reservoir exhibits various different profile and characteristics. The average sediment distribution at deeper depths closer to the trash screen was found to be of 27% clay, 26% silt, 43% sand and 4% gravel. The rehabilitation works on structure as the low level outlet serves as an important feature for reservoir sedimentation management as well as for safe flood discharge release as designed for the dam. It is important that the function of the reservoir outlet structure is maintained in accordance to the International Dam Safety Standards. © (2014) Trans Tech Publications, Switzerland.